The Research Trends and the Effectiveness of Smart Learning. (19th May 2014) - Ha, Ilkyu; Kim, Chonggun
Abstract : The introduction of useful microblogging services like Twitter derives significant changes in various areas of society. The smart tools such as mobile devices and microblogging services have led to great changes in the traditional way of education. It is possible to access good quality educational contents and methods in a more convenient way. Although a lot of smart tools have been applied for educational application, there are only limited researches that demonstrate the educational effectiveness of smart tools through experiment considerations. In this study, research documents about smart learning from 2007 have been treated based on 5 major searching sites; we investigate the research trends of smart learning of education. The opinion of the researchers about the educational use of smart tools is analyzed. Then, through substantial experiment, we are acquainted that the smart tools have a positive effect on the educational environment. As a practical application, the Twitter microblogging service is used for educational communications in 2 classes of a university during a semester. As a result, we can find that smart tools contribute to increase the efficiency of education, but learners and teachers need to pay considerable efforts on the use of smart tools to achieve the purpose.